Baselines and Updating a Project with Oracle Primavera P6 PPM - Harris, Paul (Packt Publishing, 2021)
Primavera P6 Version 8 to Version 20, this module explains the differences between the versions. About This Video Learn how to create baselines and update a project using Project Manager P6 PPM Professional Workshop on how WBS and LOE activities work, and create and assign a baseline Workshop on the project's progress and compare with the baseline set In Detail Primavera is an enterprise project portfolio management software. It includes project management, scheduling, risk analysis, opportunity management, resource management, collaboration and control capabilities, and integrates with other enterprise software such as Oracle and SAP's ERP systems. This course aims to teach participants how to baseline and update an un-resourced project with Oracle Primavera P6 PPM Professional. You will start with understanding date fields, followed by scheduling options - general tab. The topics that you will learn further are setting the baseline and limitations on viewing baseline data, practical methods of the recording process and understanding the concepts, updating the schedule, progress spotlight and update progress, suspend and resume, scheduling the project, comparing progress with the baseline, progress line display on the Gantt chart, checking list before updating schedule, in-progress schedule checklist, and corrective actions. By the end of the course, you will successfully learn how to set baseline, compare with the baseline, and update an un-resourced project with Oracle Primavera P6 PPM Professional.